The Repercussions of AI Development on Copyright - Maram Ahmed Bahakam (International Journal of Law Research and Studies, 2026)
This research examines the rapid development of artificial intelligence technologies and the fundamental transformations they have generated in the concepts of creativity and intellectual production, which have directly impacted the copyright system, Given that AI technologies are now capable of producing creative works in a manner comparable to human authorship, several legal questions have emerged, First, the research considers whether AI technologies can be regarded as authors under copyright law by virtue of producing such works, which would necessitate the recognition of legal personality a matter that has given rise to extensive legal debate regarding the granting or denial of such status, Conversely, if AI technologies are not recognized as authors, their outputs would fall within the public domain, permitting unrestricted use or appropriation by others, Consequently, another issue arises as to whether works produced by or with the assistance of AI technologies may be afforded copyright protection, Furthermore, the research addresses the development and training of AI technologies on copyrighted works, raising questions concerning the legality of such training practices and the resulting legal liability. The study concludes that the rapid advancement of AI technologies necessitates achieving a balanced application of traditional copyright rules to ensure effective protection in the digital age.
Keywords: Copyright; Artificial Intelligence; Juridical Personal; AI Training